1992
DOI: 10.1002/tera.1420460306
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopathic effects of dichloroacetate in the fetal long‐evans rat

Abstract: Dichloroacetic acid (DCA) is a by-product of the chlorine disinfection of water and may occur in treated water at levels exceeding 100 micrograms/L. Previous studies revealed teratogenic effects, particularly heart malformations, at high doses (900-2,400 mg/kg given on days 6-15 of pregnancy). In a series of three studies, groups of 7-10 Long-Evans rats were dosed with 1,900 mg/kg of DCA on days 6-8, 9-11, or 12-15; with 2,400 mg/kg on days 10, 11, 12, or 13; and with 3,500 mg/kg on days 9, 10, 11, 12, or 13, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…Also, early embryonic development of zebrafish has been found to be similar to other mammalian species in many aspects [21]. Furthermore, the results of the present study indicate responsiveness of this species to the compound through production of types of developmental toxic effects, such as yolk sac edema, mouth malformation, and behavioral changes that have not been previously reported, besides the pre- viously observed effects in the head and heart regions of rodent embryos [11][12][13].…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Also, early embryonic development of zebrafish has been found to be similar to other mammalian species in many aspects [21]. Furthermore, the results of the present study indicate responsiveness of this species to the compound through production of types of developmental toxic effects, such as yolk sac edema, mouth malformation, and behavioral changes that have not been previously reported, besides the pre- viously observed effects in the head and heart regions of rodent embryos [11][12][13].…”
Section: Discussionmentioning
confidence: 46%
“…However, others have described its developmental toxicity in rodents [11][12][13]. In this report, DCA developmental toxicity has been demonstrated in another species, namely the zebrafish (Danio rerio).…”
Section: Discussionmentioning
confidence: 67%
“…The results remained significantly elevated (aRR 5 3.74; 95% CI 5 1.21-11.62) when infants with Down syndrome were excluded from the analysis. Given the evidence for heart defects reported in animal studies with exposure to TCE and its metabolites, TCA and DCA (Epstein et al, 1992;Johnson et al, 1998a,b;Smith et al, 1989Smith et al, , 1992, there is a need for additional study of heart defects after exposure to perc.…”
Section: Prenatal and Birth Outcomesmentioning
confidence: 97%
“…The cardiac malformations studies are particularly difficult to interpret because of the lack of clear dose-response and temporal relationships (i.e., exposures prior to pregnancy, during pregnancy, or for both periods) (42). Developmental studies with TCA and dichloroacetate (DCA) also observed cardiac malformation (47)(48)(49)(50), but estimates of maternal blood TCA levels do not appear consistent between the TCA and TCE studies (21). No effects were observed with other TCE metabolites, notably chloral hydrate and dichlorovinylcysteine (DCVC) (49,50 (46,48).…”
Section: Selection Oforal Studiesmentioning
confidence: 99%